Implementasi Kebijakan PSBB di Kota Probolinggo Keputusan Gubernur Jawa Timur Nomor 188/561/Kpts/013/2021 Tahun 2021 - Sucahyo, Imam; Fadilah, Siti Nur; Hasan Akbar, M. Hasan Akbar3; Pratama, Ervito Setya; P E, M. Andrian; Danianto, M. Eko (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Coronavirus disease (covid-19) has hit the whole world, including Indonesia. Therehave been efforts to break the chain of Covid-19 in various ways, one of which iscalled Large-Scale Social Restrictions (PSBB). The purpose of this study is tomeasure the conformity of regulations with the implementation of these regulations.The results of the study show that the implementation of Large-Scale SocialRestrictions is sufficient to help control the spread of the co-19 chain. The focus ofthis study is related to the field of education where there are still many problemsexperienced during learning.